Sorption of Clomazone in Brazilian Soils with Different Physical and Chemical Attributes1 - PEREIRA,G.A.M. (2016)
ABSTRACT Knowledge of herbicides sorption by colloids predicts its movement in the soil profile and its effectiveness in controlling weeds and crops poisoning when directly applied to the soil. This knowledge becomes even more important for herbicides which have long persistence in the soil. In this research, clomazone sorption was estimated by the biological method in Brazilian soil samples with different physical and chemical characteristics, cultivated with sugarcane crops. As an indicator of the presence of clomazone in the soil, Sorghum bicolor was used. The data relating to assessments of poisoning and accumulation of dry matter of the plants were subjected to multivariate analysis of similarity among variables. After that, clomazone doses that caused 50% of intoxication in sorghum plants grown (C50) as well as sorption ratio (SR) of the herbicide in different soil types were estimated. There was similarity greater than 80% for data regarding the percentage of intoxication and accumulated dry matter, with the option to use only those related to the first variable. RS and C50 were higher in Organosol and lower in red-yellow Latosol with and without changing the pH. It was concluded that the clomazone dose to be recommended must be differentiated for different soils, since the value of clomazone sorption in the soil is dependent on its attributes, and the organic matter content is of the utmost importance.